Preservation of fertility in children treated for cancer. Issue 6 (1st June 2003) - Wallace, W H B; Thomson, A B
Abstract : As treatment for childhood cancer has become increasingly successful, adverse effects on reproductive function are assuming greater importance. Preservation of fertility before treatment must be considered in all young patients at high risk of infertility, and provision of such services requires collaboration between oncology centres and assisted conception units. The UK Children's Cancer Study Group is planning to audit current management of preservation of reproductive function in young patients with cancer, and the British Fertility Society is preparing a voluntary code of best practice to guide and inform clinicians and scientists. Limitation of radiation exposure by shielding of the testes and ovaries should be practiced where possible and sperm banking should be offered to all sexually mature boys at risk of infertility. The rapidly advancing experimental techniques for harvesting of gonadal tissue must be considered and embarked on without unrealistic expectations, although future utilisation of the tissue is unlikely to be realised until the next decade.